The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4172/2167-0420.1000360
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinant Factors of Long Acting Contraceptive Utilization among Married Women of Reproductive Age in Adaba Town, West Arsi Zone, Oromia, Ethiopia

Abstract: Background: Ethiopia is the second most populous country in Africa. Total Fertility Rate of Ethiopia is 4.6 children per women, population growth rate is estimated to be 2.7% per year and contraceptive prevalence rate is only 29% while the unmet need for family planning is 34%. The prevalence of long acting contraceptive methods (LACMs) is very low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
5
5
1
Order By: Relevance
“…As women's education level increases, the preference of long term contraceptive method increases among married women. This agrees with studies done in Adaba, Western Ethiopia and Durame [19,20,26]. The possible explanation could be that better educated women would likely have access for information on modern contraceptive methods and their increased knowledge on modern contraceptives.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As women's education level increases, the preference of long term contraceptive method increases among married women. This agrees with studies done in Adaba, Western Ethiopia and Durame [19,20,26]. The possible explanation could be that better educated women would likely have access for information on modern contraceptive methods and their increased knowledge on modern contraceptives.…”
Section: Discussionsupporting
confidence: 90%
“…It was observed that there was increasing trend on the preference of long term contraceptive methods with increment of age category as compared to age category of 15-24. This is similar with a study conducted in Adaba town and at national level [19,25]. The educational status of women was also found to be an important predictor of long term contraceptive method preference.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, merchants by occupation more likely to utilized LTFP methods than their counter parts. Occupation of the women was associated to FP utilization in different studies conducted in Ethiopia [15, 2527]. Monthly income of the household was positively associated with LTFP utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Among these only 9.2% use LARC (7.7%-Implants & 1.5%-IUD). Different studies conducted in different parts of Ethiopia also indicated lower prevalence of LARC use [6][7][8][9][10][11][12][13]. Utilization of LARC was found to have significant association with women's sociodemographic and reproductive characteristics.…”
Section: Introductionmentioning
confidence: 97%